Information technology of questions complication determination - Шибицька, Н. М.; Тимофієва, Г. А. (Problems of Informatization and Control, 2009)
Information technology of determination of questions complication is offered in test tasks. Efficiency of its use is investigational in CASS of knowledge diagnostics. The use of such technology allows to shorten the amount of questions in test tasks and more exactly define the student level of knowledges on the different stages of teaching. It is proved that the adaptive testing abbreviates the amount of experimental information unlike other methods of determination of questions complication of test task